Ontologia e currículo: uma análise do currículo do Estado de São Paulo à luz da pedagogia freireana - Ferreira, Fernando Henrique (2025)
This study investigated the ontological conceptions present in the São Paulo curriculum, analyzing their implications in light of Paulo Freire's critical pedagogy. The research was grounded in the philosophical method of dialectical historical materialism to examine ontological formation in curriculum design, seeking to unveil the political and ideological interests used as instruments of domination. The study is structured into six chapters. The first introduces the topic, emphasizing education as a battleground between hegemonic and emancipatory projects. The second explores the polysemy of the concept of ontology in the history of philosophy, from the Greeks to the historical materialism of Marx and Lukács. The third chapter analyzes the relationship between neoliberalism and curriculum, exposing the subordination of education to capitalist interests. The fourth presents Freirean pedagogy as a critical alternative, emphasizing dialogue, political consciousness, and transformative praxis. The fifth describes the methodology, based on document analysis and dialectical historical materialism. Finally, the sixth chapter examines the São Paulo curriculum, identifying the formation of the "self-entrepreneur" as a neoliberal ontological project. The study concludes that the São Paulo State curriculum aligns with a neoliberal ontology, reducing education to market logic. In contrast, Freirean pedagogy offers a path toward a critical ontology centered on human emancipation and overcoming inequalities. This work contributes to the debate on curriculum and human formation, highlighting the need for educational practices committed to social transformation.